O direito de acesso à saúde para as usuárias do SUS: o paradoxo da universalidade x exclusão - Ribeiro, Edilene Maria Vasconcelos (2017)
The present research entitled "The controversies of the right of access to health and its relationship with users of SUS", is included in the research line Public Policies and Social Changes of the Professional Masters in Public Policy Evaluation of the Federal University of Ceará. The study was carried out at the Assis Chateaubriand Maternity School and had the objective of analyzing the access of SUS users to the referred institution. For that, eight users and five professionals were interviewed obeying the principle of data saturation. The research was based on a qualitative study with the approximation of the analytical matrix Marxist. As categories, we highlight the State, public health policy, access to health, the market and law. Data collection was performed through semi-structured interviews using a tape recorder and by means of a script applied to the users and to the health professionals inserted in the service. The central theme of the study revolved around some questions regarding the reasons that hamper or limit users' access to SUS, as well as what they do to overcome the difficulties encountered. The study gave us the background to confirm that despite some advances in health and in the institutional internal scope, guaranteeing full access to the population is quite deficient when referring to the formation of waiting lines, the difficulty in regulating consultations by the poor service, lack of investments, difficulties in locomotion and socioeconomic aspects. These difficulties evidenced the demand for private services as a way to meet the health needs of the public in question. We highlight, in the users' speech, the negative trait of the experience experienced in the health system as a whole, which reflected in the discourses when asked about the institution studied. In this sense, in view of the results, we see the need to overcome some of the impasses regarding the obstacles imposed by fragmentation, deficiency in the organization, structuring and management of public services offered as a whole, as well as the need to increase investments directed to the implementation of the especially at the local level. At the institutional internal level, we verified the need to strengthen networking through the structuring of a discussion forum, the need for qualitative and periodical research with users of the service, and the promotion of health education as a way to empower the subjects for the defense of their rights.